Learning from the Experiences of Mothers of School-Aged Children on Tenure Track during the COVID-19 Global Pandemic - McDermott, Mairi (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
How are mothers of school-aged children navigating the tenure track in the global pandemic of COVID-19? In this article, I weave my reflections with the voices of other early career academic mothers of school-aged children to tell our varied stories traversing tenure. To access these stories, I conducted synchronous and asynchronous (email) dialogic interviews with six early career academic mothers of school-aged children from a variety of disciplines, departments, and universities in North America. Although COVID-19 will likely have much longer lasting implications, this article focuses on how participants felt in March 2020 when COVID-19 physical distancing plans were widely implemented. As the interviewees suggest, time was negotiated, reorganized, and felt in different ways among academic mothers of school-aged children. There were innumerable factors shaping the various responses to COVID-19 lifeworld reconfigurations while pursuing tenure, and my hope for this article is twofold—that others are able to feel seen and heard and that universities might begin truly listening to the voices and experiences of nondominant faculty to consider reorienting their tenure cultures to be more inclusive of the diverse lifeworlds their faculty inhabit. Importantly, in their commitment to equity, diversity, and inclusion, universities ought to be reflecting on the cultures and temporalities of tenure to better attend to the decline in numbers of women through the professorial ranks. Particularly in heightened times of uncertainty and intensification of historical gender inequities compelled by the global pandemic of COVID-19, this article introduces some considerations for differently approaching and reconfiguring individualist and competitive tenure processes.